Developing Elementary School Student's Learning Independence by using Android-Based Gravity e-comic - Nova Elysia Ntobuo*; Lanto Mohamad Kamil Amali; Dewi Diana Paramata; Tirtawaty Abdjul (Jurnal Pendidikan Sains Indonesia, 2023)
Student learning independence is currently low, this is indicated by the lack of a variety of learning media used by teachers. The problem to be raised is that students are not independent in exploring their knowledge, including in science subjects (results from interviews with teachers at SDN 80 Kota Tengah). To overcome these problems, the purpose of this study is to develop an android-based gravity e-comic to increase student learning independence. The method used in this research is the R D (research development) method, the development model used to produce android-based gravity e-comics is four d, with steps namely define, design, development, disseminate. The data collection procedure is to describe the validity, practicality and effectiveness of the e-comics that are made. Data analysis uses analysis of validity, practicality, and effectiveness. The results showed that the gravity e-comic developed was valid, received positive responses from students and was very good for training the learning independence of elementary school students, so it was feasible to use in the science learning process in elementary school. The conclusion of this study is that android-based gravity e-comics are valid, practical to use in the learning process, and effective in increasing student learning independence at the elementary school level